Steering strategies for wasp inspired self propelled needles - Jette Bloemberg; David Justin Jager; Paul Breedveld; Aimée Sakes (Scientific Reports)
Abstract Positioning a thin needle into a solid substrate near a target region is difficult because the needle can easily bend and buckle. Nevertheless, in nature, female parasitic wasps can do this by using buckling prevention and steering mechanisms. This study presents a self-propelled needle that incorporates wasp-inspired steering mechanisms, specifically, the use of pretension and asymmetry within the needle segments. The needle with an outer diameter of 0.89 millimeters comprises seven parallel needle segments, with the central needle segment being either straight for a forward trajectory or prebent for steering purposes. By retracting and rotating the prebent central needle segment, the needle is capable of omnidirectional steering. The performance of the needle in tissue-mimicking phantoms was evaluated in terms of its propulsion efficiency and steering performance. The propulsion efficiency, affected by slippage of the needle segments with respect to the tissue-mimicking phantoms, was, on average, 63% ± 4% for forward motion and 55% ± 7% for steering motion. Moreover, the needle successfully steered with a mean deflection-to-insertion ratio of 0.41 ± 0.11 (i.e., radius-of-curvature of 44 mm). The proposed bioinspired needle design is a relevant step toward developing steerable needles for percutaneous interventions.